Pengaruh Opinion Leader Terhadap Persepsi Tingkat Kepercayaan Merek Asing - Sari Wijayanti (JEMAP, 2021)
The purpose of this research wanted to know about the influence of opinion leader towards the belief level of foreign brand, especially neurotropic vitamin. The data was gained from 186 responden by questionnaires and interview. Sampling method used was non probability sampling and the purposive technique to select respondents engaging health care professionals including nurse, midwife and general practicioners. Simple regression was used to exam the data. There was an influence of opinion leader on the belief level of foreign brand perception showed by t-count value (4.096) which was greater than t-table (1.973). It was concluded that individuals prefer the advice received from an experienced and knowledgeable advisor more than less skilled and less experienced advisor.